(3WHbGJ GdTGaYjIs - (3CHh HcQ Hf CMeO Hf eMeO Hf YeQ GdCSOj GdTgHj GdOeTbqj, Jbqj GdOjf , (B851 (3g`s ((3YHO GdhgGH s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY bOQ GdYdeGA hLYdge HefRdI GdfLhe ai GdSeGA hjYO , agPG eNJUQ dWja GPcQ ajg WHbGJ GdTGaYjI s
(3BNQgG (B:s
(3bhdg GKfGA JQLeI jhSa Hf GSeGYjd Hf jhSa GdCfHGHi eGJ ai ThGd SfI KdGK hYTQjf hKeGf eGjI JeJ GdWHbGJ HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B61s
Keywords: (3GdJGQjNs